Sacred Dimensions of Barong Ngelawang Sungsungan: Mythology, Process, and Performance - Sukerna, I Nyoman; Setiawan, Aris (Universitas Negeri Semarang, 2024)
This research aims to explore the sacred dimensions of the Barong Ngelawang Sungsungan based on the interconnectedness of mythology, the process of sacralization, and its sacredness in performance. During religious ceremonies, the Barong symbolizes pride, magical power, grandeur, and divinity. The ethnographic methodology is employed to gain insights into cultural aspects observed, heard, and concluded, thereby understanding cultural knowledge from the perspective of the local community. Research findings indicate that from a mythological perspective, the Barong Ngelawang Sungsungan serves functionally as a sacred symbol, reinforcing the laws of cause and effect that must be obeyed and revered and a tool for creating a harmonious life. In its holy purpose, ngelawang can be manifested as a practice to strengthen fraternal bonds, interpreted as a signal of awareness, and a means of detoxification from the natural environment to eliminate negatively oriented forces..